Effectiveness of coping strategies intervention on caregiver burden among caregivers of elderly patients with dementia. Issue 1 (17th December 2014) - Chen, Hui‐Mei; Huang, Mei‐Feng; Yeh, Yi‐Chun; Huang, Wen‐Hui; Chen, Cheng‐Sheng
Abstract Background Coping strategies are a potential way to improve interventions designed to manage the caregiver burden of dementia. The purpose of this study was to develop an intervention targeted towards improving coping strategies and to examine its effectiveness on reducing caregiver burden. Methods A controlled study design was used. Fifty‐seven caregivers of dementia patients were enrolled. Coping strategies were assessed with the Revised Ways of Coping Checklist (WCCL‐R) and caregiver burden was assessed with the Chinese version of the Caregiver Burden Inventory. The participants were randomly divided into two groups. The intervention group was offered a series of five interventions in which problem‐solving skills, knowledge of dementia, social resources, and emotional support were taught every 2 weeks, and the control group was telephoned every 2 weeks for the usual clinical management. Two weeks after the end of the intervention, we again administered the WCCL‐R and the Caregiver Burden Inventory. Two‐way repeated‐measure anova was used to evaluate the changes in coping strategies and caregiver burden. Results Forty‐six participants completed the study. No statistically significant differences were noted in the demographic data between the two groups. On the problem‐focused coping subscale on the WCCL‐R, the intervention group's mean score increased by 3.8 points, and the control group's decreased by 5.1 points (F = 7.988, P = 0.007). On the seeking social support coping subscale on the WCCL‐R, the intervention group's mean score increased by 3.8 points, and the control group's decreased by 3.1 points (F = 4.462, P = 0.04). On the Caregiver Burden Inventory, the intervention group's mean score decreased by 7.2 points, and the control group's increased by 2.2 points (F = 6.155, P = 0.017). Conclusions Psychosocial intervention can help caregivers to adopt more problem‐focused and social support coping strategies, which are beneficial in terms of reducing the caregiver burden.